Preparation method of high-strength and large-size silicon dioxide aerogel
Through the hydrolysis and polycondensation reaction of tetraethyl orthosilicate, two aging and modification with modifying fluid, combined with supercritical drying technology, high-strength, large-sized silica aerogels were prepared, solving the problem of aerogel strength The problem of low and uneven microstructure significantly improves the thermal insulation performance.
Patent Information
- Application Number
- CN202411254649.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-09-09
AI Technical Summary
The low strength and poor toughness of silica aerogels lead to the fact that the prepared aerogels cannot be directly applied to the thermal insulation layer, and are prone to shrinkage and collapse during the drying process, affecting the thermal insulation performance.
Through the hydrolysis and polycondensation reaction of tetraethyl orthosilicate, combined with two aging and modification with modifying liquid, supercritical drying technology is used to prepare high-strength and large-sized silica aerogels.
A silica aerogel with high specific surface area, porosity, large size, high strength, and green environmental protection has been realized, which solves the problems of aerogel with low strength, difficulty in molding, uneven microstructure, and easy moisture absorption, and improves Improved thermal insulation performance.
Smart Images

Figure CN119330360A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of aerogel material preparation, and in particular to a method for preparing high-strength and large-sized silicon dioxide aerogel. Background Art
[0002] Silica aerogel is a lightweight nanoporous material with the characteristics of low density, high porosity (porosity is 80% to 99.8%), large specific surface area, and low thermal conductivity (its thermal conductivity coefficient is 0.013W / (m·K)). In recent years, due to its excellent thermal insulation performance, non-toxicity, and excellent environmental protection performance, silica aerogel has been widely used in heat insulation, high temperature resistance, fire prevention and other fields, and has good application prospects in the field of thermal insulation materials.
[0003] However, the low strength and poor toughness of silica aerogels make it impossible to directly apply the prepared silica aerogels to thermal insulation layers, which seriously restricts the application field of silica aerogels. At the same time, the low-strength gel skeleton structure will have shrinkage holes and collapse during the drying process, which will reduce the thermal insulation performance of the aerogel structure. And due to shrinkage holes and collapse, the microstructure of silica aerogels will be uneven, and when the aerogel structure is used for fireproofing and heat insulation, the thermal insulation effect will be uneven, and local temperature convergence points will appear, further affecting the overall thermal insulation performance of the aerogel structure. In addition, silica aerogels also have the problem of absorbing moisture when encountering water, causing the skeleton structure to expand and rupture, which will also reduce the thermal insulation performance of the aerogel structure. Summary of the invention
[0004] In view of the problems existing in the above prior art, the object of the present invention is to provide a method for preparing high-strength and large-size silica aerogel, which can effectively solve the problems of low strength, difficult molding, uneven microstructure, easy moisture absorption, etc. of silica aerogel, thereby obtaining an aerogel structure with stable microstructure (i.e., not prone to shrinkage holes, collapse, skeleton structure rupture, etc.), good uniformity, low thermal conductivity, and excellent thermal insulation performance.
[0005] The purpose of the present invention is achieved through the following technical solutions: A method for preparing high-strength, large-size silica aerogel, comprising: Step S1, wet gel preparation: tetraethyl orthosilicate, anhydrous ethanol, deionized water and acid solution are uniformly mixed, and then hydrolyzed. After the hydrolysis, ammonia water is added and stirred, and then the mixture is allowed to stand for a period of time to obtain a wet gel; Step S2, aging: adding the wet gel to an aging solution at room temperature for primary aging, and then performing secondary aging in anhydrous ethanol in a water bath environment; Step S3, surface modification: adding the aged gel to the modification solution, performing modification twice or more, and replacing with anhydrous ethanol solution after the modification; Step S4, drying: supercritical drying is used to dry the modified gel solution to obtain a silica aerogel block.
[0006] Based on further optimization of the above scheme, the volume ratio of tetraethyl orthosilicate, anhydrous ethanol, deionized water and acid solution is 4.5-6.5:13-17:0.8-1.2:0.3-1; the acid solution adopts any one of nitric acid, hydrochloric acid or phosphoric acid.
[0007] Based on further optimization of the above scheme, the hydrolysis step in step S1 is: placing in a water bath at a temperature of 45 to 65° C. for hydrolysis for 8 to 16 hours.
[0008] Based on further optimization of the above scheme, the volume ratio of the ammonia water to the acid solution is 1:0.3-1, and the stirring time after adding the ammonia water is 3-5 minutes.
[0009] Based on further optimization of the above scheme, the standing time in step S1 is 5 to 30 minutes.
[0010] Based on further optimization of the above scheme, the aging liquid for the primary aging includes tetraethyl orthosilicate, anhydrous ethanol and ammonia water, and their volume percentages are: 12%-16%: 82%-88%: 0.8%-1.2%; the primary aging time is 5-10 hours.
[0011] Based on further optimization of the above scheme, the water bath environment temperature of the secondary aging is 40-60° C., the aging time is 48-72 h, and the anhydrous ethanol is replaced every 12-16 h.
[0012] Through the aging steps of first aging with aging liquid and then aging with anhydrous ethanol, firstly, the polymers in the aging liquid enter the network structure of the gel and continuously react with the polymers in the gel, thereby making the gel structure uniform and improving the gel strength; secondly, the water in the gel is fully replaced by the sealing effect of anhydrous ethanol on water, thereby reducing the capillary force in the network structure, avoiding the coarseness of the gel network skeleton, and the occurrence of shrinkage holes and collapse of the gel during the drying process.
[0013] Based on further optimization of the above scheme, the modified liquid is an ethanol solution with a volume fraction of 8% to 12% of the modifier; wherein the modifier is composed of trimethylethoxysilane, dimethyldiethoxysilane and methyltriethoxysilane, and the volume ratio between them is 0.7 to 1.3:1.8 to 2.2:6.5 to 7.5; the modification time of the modified liquid each time is 22 to 26 hours.
[0014] The present application modifies the aged wet gel by using a modifier composed of trimethylethoxysilane, dimethyldiethoxysilane and methyltriethoxysilane. Firstly, the hydrophobic group Si-CH3 reacts with the silanol Si-OH in the gel and is grafted onto the surface of the gel to present hydrophobicity, thereby avoiding the skeleton cracking caused by the gel absorbing moisture when in contact with water. Secondly, no unnecessary by-products are produced during the reaction of the modifier, which is green and environmentally friendly. Thirdly, the grafted oxysilane is used to enhance the surface stability of the gel. Fourthly, a modifier composed of multiple groups is used to enhance the skeleton strength of the gel and improve the overall strength of the gel by utilizing multiple hydrophobic groups, and a single hydrophobic group is used to increase the chain length of the gel and restrict the shrinkage problem caused by the continuous reaction of multiple hydrophobic groups, thereby ensuring the porosity of the silica aerogel finally obtained and the uniformity of the microstructure.
[0015] Based on the further optimization of the above scheme, the supercritical drying step is specifically as follows: First, the modified gel solution is slowly placed in a drying kettle, and the drying kettle is sealed; then, the temperature of the drying kettle is increased to maintain at 40-60°C, and CO2 is pumped into the drying kettle to increase the pressure to 10-15MPa, so as to extract anhydrous ethanol, and the extracted anhydrous ethanol is discharged from the separation kettle; the drying time is 4-12h, and after drying, the pressure relief valve is opened to release the pressure, and the pressure relief rate is 0.2-2.0MPa / h.
[0016] The following are the effects of the technical solution of the present invention: The present application prepares a silica aerogel with high specific surface area, high porosity, large size, high strength and green environmental protection by means of hydrolysis and polycondensation reaction of tetraethyl orthosilicate, combined with two aging processes (i.e., one aging process with aging liquid and two aging processes with anhydrous ethanol), modification with modifying liquid and supercritical drying. Through the two aging processes, not only tetraethyl orthosilicate is fully hydrolyzed and polycondensed to improve the uniformity of the gel, but also the water in the gel is effectively replaced and the capillary force in the skeleton structure is reduced; then, with the aid of a specific proportion of modifiers, not only the skeleton structure of the gel is enhanced, but also the water absorption of the gel surface is solved, and the surface stability and internal porosity of the gel are also improved, thereby effectively improving the fireproof and heat-insulating properties of the aerogel structure. The overall process means of the present application are simple and feasible, the materials used are common and easily available, the preparation cost is low, and it is suitable for industrial and large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 This is a physical picture of the sample of silica aerogel prepared in the example of the present invention.
[0018] Figure 2 The microstructure diagram of the silica aerogel prepared in the embodiment of the present invention.
[0019] Figure 3 Schematic diagram of the structure of the supercritical drying device in an embodiment of the present invention.
[0020] Figure 4 : This is the N2 adsorption-desorption curve of the silica aerogel prepared in the example of the present invention.
[0021] Figure 5 This is a pore size distribution diagram of the silica aerogel prepared in the embodiment of the present invention.
[0022] Figure 6 The microstructure and physical picture of the silica aerogel prepared in Comparative Example 3 of the present invention; wherein, Figure 6 (a) is the microstructure, Figure 6 (b) is the actual picture.
[0023] Among them, 10, drying kettle; 20, separation kettle; 30, CO2 gas cylinder. DETAILED DESCRIPTION
[0024] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly described below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.
[0025] Embodiment 1: A method for preparing high-strength, large-size silica aerogel, comprising: Step S1, wet gel preparation: first, tetraethyl orthosilicate, anhydrous ethanol, deionized water and acid solution are uniformly mixed, wherein the volume ratio of tetraethyl orthosilicate, anhydrous ethanol, deionized water and acid solution is 4.5:13:0.8:0.3, and nitric acid is used as the acid solution; then, put it into a water bath at a temperature of 45°C for hydrolysis for 16 hours; after hydrolysis, add ammonia water and stir for 3 minutes (the stirring rate is set according to the actual situation, and it only needs to ensure that the ammonia water and the mixed solvent are fully in contact), and the volume ratio of ammonia water to the acid solution is 1:0.3; then let it stand for 10 minutes to obtain a wet gel.
[0026] Step S2, aging: the wet gel is added to an aging solution at room temperature for one aging (the room temperature in this embodiment is 24-26° C.), the aging solution comprises tetraethyl orthosilicate, anhydrous ethanol and ammonia water, and their volume percentages are: 12%: 87.2%: 0.8%; the aging time is 10 hours.
[0027] Then, the sample was aged for a second time with anhydrous ethanol in a water bath environment. The water bath environment temperature was 40°C, the aging time was 64 hours, and the anhydrous ethanol was replaced every 16 hours (i.e., the anhydrous ethanol was replaced three times).
[0028] Step S3, surface modification: adding the aged gel to a modification liquid and performing two modifications, wherein the modification liquid is an ethanol solution of a modifier with a volume fraction of 8%; wherein the modifier is composed of trimethylethoxysilane, dimethyldiethoxysilane and methyltriethoxysilane, and the volume ratio thereof is 0.7:1.8:6.5; each modification time of the modification liquid is 26 hours (i.e., the modification liquid is replaced every 26 hours).
[0029] After the modification, anhydrous ethanol solution was used for replacement.
[0030] Step S4, drying: drying the modified gel solution by supercritical drying (supercritical drying device such as Figure 3 As shown), specifically: First, slowly put the modified gel solution into the drying kettle and seal the drying kettle; then, heat the drying kettle and keep its temperature at 40°C, and then pump CO2 into the drying kettle (by means of CO2 cylinder and opening V4 valve) to pressurize the drying kettle, so that the pressure of the drying kettle rises to 10MPa, and the anhydrous ethanol is extracted. The extracted anhydrous ethanol is discharged from the separation kettle; the drying time is 12h. After drying, open the pressure relief valve (i.e. Figure 3 The pressure relief is carried out through the V5 valve shown in the figure, and the pressure relief rate is 1.0MPa / h.
[0031] Finally, a silica aerogel block is obtained.
[0032] Embodiment 2: A method for preparing high-strength, large-size silica aerogel, comprising: Step S1, wet gel preparation: first, tetraethyl orthosilicate, anhydrous ethanol, deionized water and acid solution are uniformly mixed, wherein the volume ratio of tetraethyl orthosilicate, anhydrous ethanol, deionized water and acid solution is 5.5:15:1:0.6, and hydrochloric acid is used as the acid solution; then, it is placed in a water bath at a temperature of 55°C for hydrolysis for 12 hours; after hydrolysis, ammonia water is added and stirred for 4 minutes (the stirring rate is set according to the actual situation, and it only needs to ensure that the ammonia water and the mixed solvent are fully in contact), and the volume ratio of ammonia water to the acid solution is 1:0.6; then it is allowed to stand for 20 minutes to obtain a wet gel.
[0033] Step S2, aging: the wet gel is added to an aging solution at room temperature for one aging (the room temperature in this embodiment is 24-26° C.), the aging solution comprises tetraethyl orthosilicate, anhydrous ethanol and ammonia water, and their volume percentages are: 14%: 85%: 1%; the aging time is 7 hours.
[0034] Then, the sample was aged for a second time with anhydrous ethanol in a water bath environment. The water bath environment temperature was 50°C, the aging time was 56 hours, and the anhydrous ethanol was replaced every 14 hours (i.e., the anhydrous ethanol was replaced three times).
[0035] Step S3, surface modification: adding the aged gel to a modification liquid and performing three modifications, wherein the modification liquid is an ethanol solution of a modifier with a volume fraction of 10%; wherein the modifier is composed of trimethylethoxysilane, dimethyldiethoxysilane and methyltriethoxysilane, and the volume ratio thereof is 1:2:7; each modification time of the modification liquid is 24 hours (i.e., the modification liquid is replaced every 24 hours).
[0036] After the modification, anhydrous ethanol solution was used for replacement.
[0037] Step S4, drying: drying the modified gel solution by supercritical drying (supercritical drying device such as Figure 3 As shown), specifically: First, slowly put the modified gel solution into the drying kettle and seal the drying kettle; then, heat the drying kettle and keep its temperature at 50°C, and then pump CO2 into the drying kettle (by means of CO2 cylinder and opening V4 valve) to pressurize the drying kettle, so that the pressure of the drying kettle rises to 12MPa, and the anhydrous ethanol is extracted. The extracted anhydrous ethanol is discharged from the separation kettle; the drying time is 8h. After drying, open the pressure relief valve (i.e. Figure 3 The pressure relief is carried out through the V5 valve shown in the figure, and the pressure relief rate is 1.5MPa / h.
[0038] Finally, a silica aerogel block is obtained.
[0039] Embodiment 3: A method for preparing high-strength, large-size silica aerogel, comprising: Step S1, wet gel preparation: first, tetraethyl orthosilicate, anhydrous ethanol, deionized water and acid solution are uniformly mixed, wherein the volume ratio of tetraethyl orthosilicate, anhydrous ethanol, deionized water and acid solution is 6.5:17:1.2:1, and phosphoric acid is used as the acid solution; then, put it into a water bath at a temperature of 65°C for hydrolysis for 8 hours; after hydrolysis, add ammonia water and stir for 5 minutes (the stirring rate is set according to the actual situation, and it only needs to ensure that the ammonia water and the mixed solvent are fully in contact), and the volume ratio of ammonia water to the acid solution is 1:1; then let it stand for 30 minutes to obtain a wet gel.
[0040] Step S2, aging: the wet gel is added to an aging solution at room temperature for one aging (the room temperature in this embodiment is 24-26° C.), the aging solution comprises tetraethyl orthosilicate, anhydrous ethanol and ammonia water, and their volume percentages are: 16%: 82.8%: 1.2%; the aging time is 5 hours.
[0041] Then, the sample was aged for a second time with anhydrous ethanol in a water bath environment. The water bath environment temperature was 60°C, the aging time was 48 hours, and the anhydrous ethanol was replaced every 12 hours (i.e., the anhydrous ethanol was replaced three times).
[0042] Step S3, surface modification: adding the aged gel to a modification liquid and performing two modifications, wherein the modification liquid is an ethanol solution of a modifier with a volume fraction of 12%; wherein the modifier is composed of trimethylethoxysilane, dimethyldiethoxysilane and methyltriethoxysilane, and the volume ratio thereof is 1.3:2.2:7.5; each modification time of the modification liquid is 22 hours (i.e., the modification liquid is replaced every 22 hours).
[0043] After the modification, anhydrous ethanol solution was used for replacement.
[0044] Step S4, drying: drying the modified gel solution by supercritical drying (supercritical drying device such as Figure 3 As shown), specifically: First, slowly put the modified gel solution into the drying kettle and seal the drying kettle; then, heat the drying kettle and keep its temperature at 60°C, and then pump CO2 into the drying kettle (by opening the V4 valve and CO2 cylinder) to pressurize the drying kettle, so that the pressure of the drying kettle rises to 15MPa, and the anhydrous ethanol is extracted. The extracted anhydrous ethanol is discharged from the separation kettle; the drying time is 4h. After drying, open the pressure relief valve (i.e. Figure 3 The pressure relief is carried out through the V5 valve shown in the figure, and the pressure relief rate is 2.0MPa / h.
[0045] Finally, a silica aerogel block is obtained.
[0046] Comparative Example 1: A method for preparing a silica aerogel, comprising: Step S1, wet gel preparation: the same as step S1 in Example 2.
[0047] Step S2, aging: the wet gel is aged in anhydrous ethanol in a water bath environment, the water bath environment temperature is 50° C., the aging time is 56 h, and the anhydrous ethanol is replaced every 14 h (i.e., the anhydrous ethanol is replaced three times).
[0048] Step S3, surface modification: the same as step S3 in Example 2.
[0049] Step S4, drying: the same as step S4 in Example 2.
[0050] Comparative Example 2: A method for preparing a silica aerogel, comprising: Step S1, wet gel preparation: the same as step S1 in Example 2.
[0051] Step S2, aging: the same as step S2 in Example 2.
[0052] Step S3, surface modification: adding the aged gel to a modification liquid and performing three modifications, wherein the modification liquid is an ethanol solution with a volume fraction of 10% of a modifier; wherein the modifier is trimethylethoxysilane; and each modification time of the modification liquid is 24 hours (i.e., the modification liquid is replaced every 24 hours).
[0053] After the modification, anhydrous ethanol solution was used for replacement.
[0054] Step S4, drying: the same as step S4 in Example 2.
[0055] Comparative Example 3: A method for preparing a silica aerogel, comprising: Step S1, wet gel preparation: the same as step S1 in Example 2.
[0056] Step S2, aging: the same as step S2 in Example 2.
[0057] Step S3, surface modification: adding the aged gel to a modification liquid and performing three modifications, wherein the modification liquid is an ethanol solution with a volume fraction of 10% of a modifier; wherein the modifier is composed of methyltriethoxysilane; and each modification time of the modification liquid is 24 hours (i.e., the modification liquid is replaced every 24 hours).
[0058] After the modification, anhydrous ethanol solution was used for replacement.
[0059] Step S4, drying: the same as step S4 in Example 2.
[0060] Comparative Example 4: A method for preparing a silica aerogel, comprising: Step S1, wet gel preparation: the same as step S1 in Example 2.
[0061] Step S2, aging: the same as step S2 in Example 2.
[0062] Step S3, surface modification: adding the aged gel to the modification liquid and performing three modifications, wherein the modification liquid is an ethanol solution with a volume fraction of 10% of the modifier; wherein the modifier is trimethylethoxysilane and dimethyldiethoxysilane, and the volume ratio thereof is 1:2; each modification time of the modification liquid is 24 hours (i.e., the modification liquid is replaced every 24 hours).
[0063] After the modification, anhydrous ethanol solution was used for replacement.
[0064] Step S4, drying: the same as step S4 in Example 2.
[0065] The aerogel samples prepared in Examples 1 to 3 and Comparative Examples 1 to 4 were subjected to N2 adsorption and desorption tests under the same conditions (i.e., the same ambient temperature, humidity, etc.) using a fully automatic specific surface area analyzer. The corresponding pore parameters were calculated according to the BET model, and the porosity calculation formula was: ; Where: ρ b , s are the apparent density and skeleton density, ρ s The value is 2.2g / cm 3 ; At the same time, the thermal conductivity of the aerogel samples prepared in Examples 1 to 3 and Comparative Examples 1 to 4 at 25° C. was tested according to the standard GB / T10294-2008 "Determination of Steady-State Thermal Resistance and Related Properties of Insulating Materials - Guarded Hot Plate Method". The test results are as follows:
[0066] In addition, the N2 adsorption-desorption curve and pore size distribution of the silica aerogel prepared in Example 2 of the present application are as follows: Figure 4 , Figure 5 As shown (the N2 adsorption-desorption curves and pore size distribution of the silica aerogels prepared in Examples 1 and 3 are consistent with those in Example 2), the average pore size of the silica aerogel in the present application is obtained to be 13.23 nm.
[0067] In addition, silica is difficult to shape due to its high porosity and usually exists in the form of fragments (see Figure 6 (b) shows the actual picture of the silica aerogel prepared in Examples 1 to 3. Figure 1 As shown, it is a complete structure (i.e., there is no collapse, shrinkage, etc. during the supercritical drying process). The silica aerogels prepared in Comparative Examples 1, 2, and 4 are substantially the same as those in the embodiments of the present application; the silica aerogel prepared in Comparative Example 3 is as shown in FIG. Figure 6 As shown in (b), it is in the form of fragments, that is, collapse and shrinkage occur, resulting in overall dispersion. Therefore, it is proved that the silica aerogel prepared by the method of the present application not only has a larger specific surface area and a higher porosity, but also has a higher strength, so as to avoid the problems of collapse and shrinkage during the drying process.
Claims
1. A method for preparing high-strength, large-size silica aerogel, characterized in that: include: Step S1, wet gel preparation: tetraethyl orthosilicate, anhydrous ethanol, deionized water and acid solution are uniformly mixed, and then hydrolyzed. After the hydrolysis, ammonia water is added and stirred, and then the mixture is allowed to stand for a period of time to obtain a wet gel; Step S2, aging: adding the wet gel to an aging solution at room temperature for primary aging, and then performing secondary aging in anhydrous ethanol in a water bath environment; Step S3, surface modification: adding the aged gel to the modification solution, performing modification twice or more, and replacing with anhydrous ethanol solution after the modification; Step S4, drying: supercritical drying is used to dry the modified gel solution to obtain a silica aerogel block.
2. The method for preparing a high-strength, large-size silica aerogel according to claim 1, characterized in that: The volume ratio of tetraethyl orthosilicate, anhydrous ethanol, deionized water and acid solution is 4.5-6.5:13-17:0.8-1.2:0.3-1; the acid solution is any one of nitric acid, hydrochloric acid or phosphoric acid.
3. A method for preparing a high-strength, large-size silica aerogel according to claim 1 or 2, characterized in that: The hydrolysis step in step S1 is: placing in a water bath at a temperature of 45 to 65° C. for hydrolysis for 8 to 16 hours.
4. A method for preparing a high-strength, large-size silica aerogel according to any one of claims 1 to 3, characterized in that: The volume ratio of the ammonia water to the acid solution is 1:0.3-1, and the stirring time after adding the ammonia water is 3-5 minutes.
5. A method for preparing a high-strength, large-size silica aerogel according to any one of claims 1 to 3, characterized in that: The standing time in step S1 is 5 to 30 minutes.
6. The method for preparing a high-strength, large-size silica aerogel according to claim 1, characterized in that: The aging liquid for the primary aging includes tetraethyl orthosilicate, anhydrous ethanol and ammonia water, and their volume percentages are: 12%-16%: 82%-88%: 0.8%-1.2%; the primary aging time is 5-10 hours.
7. The method for preparing a high-strength, large-size silica aerogel according to claim 1, characterized in that: The water bath environment temperature of the secondary aging is 40-60° C., the aging time is 48-72 hours, and the anhydrous ethanol is replaced every 12-16 hours.
8. The method for preparing a high-strength, large-size silica aerogel according to claim 1, characterized in that: The modified liquid is an ethanol solution with a volume fraction of 8% to 12% of the modifier; wherein the modifier is composed of trimethylethoxysilane, dimethyldiethoxysilane and methyltriethoxysilane, and the volume ratio thereof is 0.7 to 1.3:1.8 to 2.2:6.5 to 7.5; and the modification time of the modified liquid each time is 22 to 26 hours.